Reimagining Preexposure Prophylaxis Provision for Women in the United States. (28th April 2022) - Seidman, Dominika; Logan, Rachel; Weber, Shannon; Gandhi, Anisha; Blackstock, Oni
Abstract: Structural determinants of health drive inequities in the acquisition of human immunodeficiency virus (HIV) and the use of preexposure prophylaxis (PrEP) for HIV prevention among cisgender women in the United States. However, current PrEP clinical guidance and implementation paradigms largely focus on individual behaviors and characteristics, resulting in missed opportunities to improve PrEP access, and the implicit transferring of prevention work from health systems to individuals. In this viewpoint article, we outline ways to apply a structural lens to clinical guidance and PrEP implementation for women and propose areas for future work. Abstract : To address the structural drivers of human immunodeficiency virus acquisition in cisgender women in the United States, a structural lens must be applied to preexposure prophylaxis clinical guidance and implementation.